Relict root left in the mandible after extraction of the teeth 35 as a causative agent of the inflammation process in the region of mental foramen of the mandible - Dawid Zagacki; Piotr Pietryka; Monika Ratajek-Gruda; Anna Janas-Naze (Kazimierz Wielki University, 2021)
We present a case of iatrogenic complication after extraction of the teeth 35 in 63-years old women. There was a root of the teeth left in the bone. It was a causative agent of pain sensations and inflammation of the surrounding tissues. Due to the close distance between the root, mandible canal and mental foramen of mandible the removal of relict root was burden with high risk of parasthesis.